Phase Behavior of Poly(D-lactic acid), Dichloromethane, and Carbon Dioxide Ternary Mixture Systems at High Pressure - Gwon, Jungmin; Kim, Soo Hyun; Shin, Hun Yong; Kim, Hwayong (AMER CHEMICAL SOC, 2014)
The phase behavior of a poly(D-lactic acid) (M-w = 359 000 g/mol, polydispersity 1.7), carbon dioxide, and dichloromethane ternary system was measured by a variable-volume view cell. The experimental temperatures and pressures ranged from 313.15 to 363.15 K, up to 300 bar as various experimental conditions of the CO2/dichloromethane mass ratio and temperature, at poly(D-lactic acid) mass fractions of 1.0, 2.0, and 3.0%. The correlation results were obtained from the hybrid equation of state (Peng-Robinson equation of state + SAFT equation of state) using the van der Waals one-fluid mixing rule for the polymer-CO2-solvent system. The binary interaction parameters were optimized by the simplex method algorithm.